MANAJEMEN PENGEMBANGAN KURIKULUM BERBASIS KKNI - FATHONI, AHMAD (Universitas Islam Negeri Raden Intan Lampung, 2015)
KKNI embodies the quality and identity of the Indonesian nation associated with national education and training system is owned by Indonesia. (Presidential Decree No. 8 of 2012). In KKNI perspective, every program of study is required to clarify the